2020
DOI: 10.1007/s12325-020-01442-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Transmission of SARS-CoV-2 Through the Ocular Surface and its Detection in Tears and Conjunctival Secretions: A Review

Abstract: SARS-CoV-2 is a highly transmissible virus that spreads mainly via person-to-person contact through respiratory droplets, or through contact with contaminated objects or surfaces from an infected person. At present we are passing through a phase of slow and painful understanding of the origin, epidemiological profile, clinical spectrum, and risk profile of the virus. To the best of our knowledge there is only limited and contradictory evidence concerning SARS-CoV-2 transmission through other routes. Importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
(47 reference statements)
1
28
0
Order By: Relevance
“…Reassuringly, spatter did not extend above the neckline of the surgeons' scrub gown; sparing the surgeons' head, surgical mask and eyewear nor did spatter contaminate the assistant or equipment table. We therefore conjecture through our observed locally‐limited microdroplet spatter and in the context of a lack of convincing evidence of viable SARS‐CoV‐2 in the tear film, 19,24,25 that the risk of contamination is relatively low and only standard PPE equipment is required for the operating surgeon, assistant and the circulating theatre staff.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Reassuringly, spatter did not extend above the neckline of the surgeons' scrub gown; sparing the surgeons' head, surgical mask and eyewear nor did spatter contaminate the assistant or equipment table. We therefore conjecture through our observed locally‐limited microdroplet spatter and in the context of a lack of convincing evidence of viable SARS‐CoV‐2 in the tear film, 19,24,25 that the risk of contamination is relatively low and only standard PPE equipment is required for the operating surgeon, assistant and the circulating theatre staff.…”
Section: Discussionmentioning
confidence: 95%
“…Despite this, previous pilot studies and experiments have demonstrated that piezosurgical procedures can and do produce both microdroplets and aerosolized particles 10,12,27 . By the nature of clinical and surgical practice, ophthalmologists may be at risk of exposure to SARS‐CoV‐2 5,19,24,28 . However, while both microdroplets and exhaled aerosol have been identified as potential routes for SARS‐CoV‐2 transmission, the risk of viable viral contamination via ocular fluid, through the generation of microdroplets and aerosol during phacoemulsification surgery, appears to be low but is still under investigation 4,23,25,26,29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus that causes COVID-19 is transmitted through respiratory aerosols or physical contact with contaminated droplets [4]. SARS-CoV-2 virus then finds its way into the respiratory system, where they induce a cascade of inflammatory reactions [4]. SARS-CoV-2-induced COVID-19 has caused a large variety of complications resulting in high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2-induced COVID-19 has caused a large variety of complications resulting in high morbidity and mortality. COVID-19-induced pathologies are not limited to the respiratory system alone, but they are also seen in other body systems and organs such as the brain [5], eye [4], gastrointestinal tract [6], renal and urinary structures [7], hemopoietic [8], and cardiovascular [9] system. Recent reports show that COVID-19 causes several cardiovascular complications including myocardial infarction (MI), myocarditis, heart failure (HF), cardiogenic shock, and sudden cardiac death (SCD) [10].…”
Section: Introductionmentioning
confidence: 99%